CIAT Forages - Maass, Brigitte L. (2011)
In this short clip from our Annual Program Review in Nairobi, Kenya, last week, CIAT forages scientist Brigitte Maas gives a quick overview of her work in Africa, and the potential of particular forage crops for improving guinea pig production, improving rural nutrition and incomes, and empowering women in Democratic Republic of Congo.